PENGARUH KINERJA LINGKUNGAN DAN GREEN INVESTMENT TERHADAP PENGUNGKAPAN EMISI KARBON - Indah Mutiara Dani; Puji Harto (Diponegoro Journal of Accounting, 2022)
This study aims to examine the Effect of Environmental Performance and Green Investment on Disclosure of Carbon Emissions with the theories used are legitimacy theory. This study uses a quantitative approach using secondary data. The research method used is the documentation method with data collection based on the company's annual report and sustainability report. The sample in this study are companies that are members of the SR-KEHATI Index on the Indonesia Stock Exchange in 2016-2020 with the sampling method using purposive sampling. The number of samples obtained is 82 companies from 125 companies that are used as the population. The data analysis technique used in this study is a multiple linear regression analysis model. This study found that the environmental performance variable has a positive effect on the disclosure of carbon emissions. The results also reveal that green investment has no significant effect on the disclosure of carbon emissions.